SISTEM PEMBAGIAN HAK WARIS PADA MASA BALI KUNO ABAD IX – XII MASEHI - I Made, Hendy Lila Winarta (Humanis, 2015)
Inheritance is a gift from the ancestors through the parents, the offspring can be a moving object or not. Inheritance in Bali can’t be separated from the family, especially the kinship system generally adopted. Early emergence during the process of inheritance of ancient Bali is found in some ancient inscriptions of which the inscription Sukawana A1. The purpose of this study provide direction for the author to the next step on the activities and address the three issues raised in this research that is what a legacy that can be inherited, the system used, and the party entitled to receive the inheritance of ancient Bali during Century IX - XII AD . The theory used in this research is the theory of structural functionalism and theory of gender inequality. This research was conducted by using literature data collection methods, as well as the method of processing data through qualitative analysis, contextual and comparative descriptive. Based on the analysis results can be seen some kind of inherited the estate, all household furnishings, livestock, servants (slave), follower, fields, and gardens. The system used in distributed legacy is suhunan tanggungan use the term implies 2 : 1, the two parts to be widowed husband and the wife's part to become widows. The party entitled to receive the inheritance that the officials, the king, presented to the gods, and for the sacred building .
Keywords: suhunan tanggungan, inheritance, and ancient Bali